Quality Improvement Project in the introduction of Major Trauma and Major Haemorrhage Protocol - Debkumar Chowdhury (International Journal of Medical Research and Review, 2022)
Introduction: We recognised there was a need for a set criterion for the activation of MHP andMTTA at our Trust. The main aim is to streamline the trauma care that our patients would receivearound the clock. Ours is a large Major Trauma Unit regularly receiving a large volume of traumapatients of varying severity of injury Objective: The use of a checklist for the initial management of MTTA and MHP to ensure the process is streamlined and led by the trauma team leader. This wouldhelp reduce the cognitive load that is often presented to the team leader. This would also help directjunior team members with limited experience in the initial management of major trauma. Method/Intervention: An initial survey about MTTA and MHP from senior clinicians was carriedout. Several teaching sessions were undertaken. In addition to this, an algorithm for the initialmanagement in terms of transfer protocol was also introduced. Results: From the clinicians’perspective, 89% of the respondents felt that the use of MHP and MTTA protocol would reduce thecognitive load whilst managing major trauma. There was an improvement in the level of confidenceof clinicians in the initial management of major trauma from 52.9 % to 89%. Conclusion: Throughthis project, we hope that there is a better understanding of the need to have pre-defined criteria foractivation for MTTA and MTP for several reasons as highlighted in the article. The eventual aim of theproject is to streamline the initial management of the majorly injured patient and undertake thenecessary practical steps.